Constraints and Barriers in Handling Severe Preeclampsia - Windu Reswari; Fatmawati Fatmawati; Ema Julita; Lelly Deswitri; Rahmadevita Rahmadevita (GLOBAL HEALTH SCIENCE GROUP, 2026)
WHO 2020 data shows a Maternal Mortality Rate (MMR) of 223 per 100,000. The Indonesian Health Profile in 2023, MMR in Indonesia is 189 per 100,000 live births. The most common causes of death are hypertension in pregnancy (412 cases), obstetric hemorrhage (360 cases) and other obstetric complications (204 cases). Preeclampsia is the most common hypertension in pregnancy in Indonesia, 7-10% of all pregnancies. Preeclampsia causes >70,000 maternal deaths and 500,000 fetal deaths worldwide each year. This study aims to explore in depth the obstacles and constraints in the management of severe preeclampsia at Dr. M. Djamil Padang General Hospital in 2025. Qualitative research methods. Informants were selected purposively with the following criteria: medical and nursing service managers, obstetrician/gynecologist specialists, midwives and nurses (in the emergency room or delivery room, obstetrics polyclinic, obstetrics inpatient, operating room, intensive care unit, and NICU), working for at least 1 year, directly involved in the management of severe preeclampsia, patients or their families. The number of informants was determined based on the saturation principle. Data collection techniques were in-depth interviews, field observations, document analysis, and FGDs. Data collection instruments used interview guidelines, voice recorders (with permission), and field notes. The analysis used was thematic. Data validity was verified by triangulation. Research results: Main strengths: the system is standardized (SOP, financing, evaluation). Main weaknesses: human resources, facilities, communication, and logistics. Biggest opportunities: strengthening the referral system and increasing human resources capacity. The main threat of patient overload due to referrals and delays in PEB management is influenced by several factors, including input, process, and output aspects of the healthcare system. Input Aspects (Men, Money, Methods)